Esophageal Involvement and Bleeding in Bullous Pemphigoid Disease - Kerem Kenarlı; Derya Arı; Musa Caner Yılmaz (Caucasian Medical Journal)
Bullous pemphigoid (BP) is the most common autoimmune bullous disorder and is characterized by autoantibodies against hemidesmosomal proteins in the skin and mucous membranes. BP typically presents as large, fluid-filled blisters on normal skin or red, enflamed areas of skin, mainly in the armpits, lower abdomen, inner thighs, and groin. Blisters on the lining of the oral and pharyngeal mucosa occur in up to 35% of cases, but blisters in the esophagus are rare, especially when there are no oral blisters. We report a case of newly diagnosed BP in a 48-year-old woman. She was admitted to our hospital with the sudden onset of hematemesis. This case highlights the importance of gastroenterologists who are cognizant of the potential association between skin illnesses and digestive disorders. It is important to exercise caution during endoscopic procedures in patients with pemphigoid disorders, especially in the absence of apparent symptoms.